Optimalisasi Penempatan UPFC Pada Sistem Jawa Bali 500kv Menggunakan Algoritma Genetika - Danu Firmansyah; Istiyo Winarno (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2018)
The transmission network is an important part of the power system to deliver electrical energy from the power plant to the load, therefore the power system must be maximized to achieve optimal power flow, Unified Power Flow Control (UPFC) is one of the Flexible AC Transmission System (FACTS ) capable of controlling the power of the transmission line separately on electrical transmission and can be mounted on both the sender and the receiving end of the power. The UPFC power injection model to the transmission line is made in a power flow equation. In the Java Bali (Jali) 500 kV system analyzed by the Genetic Algorithm method, to produce a power injection that minimizes the active and reactive power losses of the transmission line without exceeding the UPFC device limit. In the Java Bali (Jali) 500 kV system analyzed by Genetic Algorithm method, the optimum UPFC value of Reactive Power injected to the system for bus 39 is 9695.593207MVar, bus 15 is 10598.78754 MVar, and on bus 37 is10755.88608 MVar. The total loss of channel power on the system prior to installation of UPFC is1815.775809 MW, while the total loss of channel power in the system after installing UPFC with GA is1537.391648 MW.